Securitization and moral hazard: Evidence from a lender cutoff rule - Ryan Bubb; Alex Kaufman (Federal Reserve Bank of Boston, 2009)
Credit score cutoff rules result in very similar potential borrowers being treated differently by mortgage lenders. Recent research has used variation induced by these rules to investigate the connection between securitization and lender moral hazard in the recent financial crisis. However, the conclusions of such research depend crucially on understanding the origin of these cutoff rules. We offer an equilibrium model in which cutoff rules are a rational response of lenders to perapplicant fixed costs in screening. We then demonstrate that our theory fits the data better than the main alternative theory already in the literature, which supposes cutoff rules are exogenously used by securitizers. Furthermore, we use our theory to interpret the cutoff rule evidence and conclude that mortgage securitizers were in fact aware of and attempted to mitigate the moral hazard problem posed by securitization.
Keywords: D82; G01; G18; G21; G24; G28; N22; 330; Securitization; Moral Hazard; Asymmetrische Information; Subprime-Hypothek; Kreditwürdigkeit; Finanzmarktkrise; Theorie; USA